MENGUNGKAP INDEPEDENSI AUDITOR INTERNAL DALAM MENGAUDIT DAN MENDETEKSI FRAUD - rohmaniyah rohmaniyah; Fitriana Leily Nur Indah; Rahayu Runik Puji (Al-Amien Prenduan for Islamic Institute, 2021)
This study aims to determine the attitude of the independence of internal auditors when detecting and auditing fraud.This research is a qualitative research with a literature review approach.The data used is secondary data..Secondary data that has been colected is analyzed and developed to answer and describe research problems.The result of the research analysis,namely the Internal auditor must have an attitude of independence and adequate competence in the auditor when carrying out his responsibilities in detecting and preventing fraud.